Analisis Kesalahan Siswa Berdasarkan Teori Newman pada Materi Pecahan - Azra Fauzi; Sindi Nur Diansyah (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The purpose of this study is to describe errors in problems solving according to Newman's theory on the questions of pre test and post test. Newman's theory states that there are 5 phases in solving problems, its: 1) reading, 2) understanding, 3) transformation, 4) process, and 5) endcoding. The subjects of this study were 3 grade VII students of Junior High School of Aisyiyah Boarding School Malang. The pretest results were analyzed then concluded that students still made a lot of mistakes, in an effort to minimize mistakes researchers used interactive media as learning media. Post test results showed good differences in the score before and after the use of the media.